A HEALTHY LIFESTYLE AS A DETERMINANT OF FAMILY WELL-BEING IN PREPARING YOUNG PEOPLE FOR INDEPENDENT LIFE - Madgafurova , Dilfuza (Универсальная индексная библиотека Евразийского журнала социальных наук, философии и культуры, 2023)
In today's fast-paced world, the concept of a healthy lifestyle has gained significant attention as it contributes to overall well-being. This scientific article explores the role of maintaining a healthy lifestyle within the context of family dynamics and how it serves as a crucial factor in preparing young individuals for independent life. The relationship between healthy behaviors, family well-being, and the successful transition to independent living is examined, highlighting the significance of fostering healthy habits from early childhood. This article aims to underscore the importance of prioritizing a healthy lifestyle as a cornerstone for family well-being, in order to enhance the developmental outcomes of young people and enable them to thrive independently.